Handbook of Megacities and Megacity-Regions 2020
DOI: 10.4337/9781788972703.00036
|View full text |Cite
|
Sign up to set email alerts
|

The financialization of real estate in megacities and its variegated trajectories in East Asia

Abstract: This chapter sheds light on the forces that drive global financial investment into the real estate markets of megacity regions across the world. Although financial approaches and metrics of valuation stem from the Anglo-American investment culture, their rooting in different institutional contexts produces varied trajectories of financialization. Hybridization dynamics are seen especially in East Asia, where local cultures and institutional arrangements were not initially fit to integrate Western investment co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Furthermore, our main results demonstrate that the real estate sector has been an important and central sector of the US economy, a claim that has been indicated by the respective literature, as well (Aalbers, 2008; Fernandez et al, 2016; Fernandez and Aalbers, 2016). Aveline-Dubach (2020), for instance, reports that in 2017 the vast majority of the 50 largest private equity real estate firms in the world were headquartered in the US. With regard to real estate investment trusts (REITs), which are entities that hold financial securities dedicated to long-term property investments, the “US accounts for 64% of the REIT market capitalization globally (US$1069 billion in 2017) with 224 publicly-traded structures” Aveline-Dubach (2020: 398).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, our main results demonstrate that the real estate sector has been an important and central sector of the US economy, a claim that has been indicated by the respective literature, as well (Aalbers, 2008; Fernandez et al, 2016; Fernandez and Aalbers, 2016). Aveline-Dubach (2020), for instance, reports that in 2017 the vast majority of the 50 largest private equity real estate firms in the world were headquartered in the US. With regard to real estate investment trusts (REITs), which are entities that hold financial securities dedicated to long-term property investments, the “US accounts for 64% of the REIT market capitalization globally (US$1069 billion in 2017) with 224 publicly-traded structures” Aveline-Dubach (2020: 398).…”
Section: Discussionmentioning
confidence: 99%
“…Aveline-Dubach (2020), for instance, reports that in 2017 the vast majority of the 50 largest private equity real estate firms in the world were headquartered in the US. With regard to real estate investment trusts (REITs), which are entities that hold financial securities dedicated to long-term property investments, the “US accounts for 64% of the REIT market capitalization globally (US$1069 billion in 2017) with 224 publicly-traded structures” Aveline-Dubach (2020: 398). The latter observation is also consistent with the empirical research on the centrality of economic sectors and the inter-sectoral linkages.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the establishment of REIT channels requires significant effort by central governments – inter alia, the creation of dedicated legal and regulatory frameworks, the transparent mediation of information and standardization of performance metrics and assessments. However, the vehicles can also be efficiently used to pursue macroeconomic goals, such as deleveraging a failing banking sector (Aveline-Dubach, 2020, 2022; Waldron, 2018) or creating an environment conducive to foreign and domestic investment in a national or urban economy (Aveline-Dubach, 2017). In the context of fiscal austerity, REITs offer state authorities ready-to-use solutions to release public capital through the large-scale privatization of welfare properties.…”
Section: The Changing Structure Of Nursing Home Ownership Amid the Fi...mentioning
confidence: 99%
“…Financialisation tendencies are geographically uneven and variegated across institutional and cultural contexts (Aveline‐Dubach 2020; Fernandez & Aalbers 2016; Pike & Pollard 2010). Research has shown how the distinctive geographies of places shape financialisation processes, such as in the way that middle‐class suburbs were targeted as a valuable market for securitisation of debt in the US (Langley 2006).…”
Section: Background: Inequality and Homeownershipmentioning
confidence: 99%